Establishment of a fluorescent reporter of RNA-polymerase II activity to identify dormant cells - Freter, Rasmus; Falletta, Paola; Omrani, Omid; Rasa, Mahdi; Herbert, Katharine; Annunziata, Francesco; Minetti, Alberto; Krepelova, Anna; Adam, Lisa; Käppel, Sandra; Rüdiger, Tina; Wang, Zhao-Qi; et al. (Nature communications, 2021)
Dormancy, a reversible quiescent cellular state characterized by greatly reduced metabolic activity, protects from genetic damage, prolongs survival and is crucial for tissue homeostasis and cellular response to injury or transplantation. Dormant cells have been characterized in many tissues, but their identification, isolation and characterization irrespective of tissue of origin remains elusive. Here, we develop a live cell ratiometric fluorescent Optical Stem Cell Activity Reporter (OSCAR) based on the observation that phosphorylation of RNA Polymerase II (RNApII), a hallmark of active mRNA transcription elongation, is largely absent in dormant stem cells from multiple lineages. Using the small intestinal crypt as a model, OSCAR reveals in real time the dynamics of dormancy induction and cellular differentiation in vitro, and allows the identification and isolation of several populations of transcriptionally diverse OSCAR high and OSCAR low intestinal epithelial cell states in vivo. In particular, this reporter is able to identify a dormant OSCAR high cell population in the small intestine. OSCAR therefore provides a tool for a better understanding of dormant stem cell biology. The identification and characterisation of dormant cells is currently difficult. Here the authors report Optical Stem Cell Activity Reporter (OSCAR) to assess RNA polymerase II activity and identify dormant cell populations in intestinal epithelial cells in vivo.